2013
DOI: 10.1038/nature12519
|View full text |Cite|
|
Sign up to set email alerts
|

Immune clearance of highly pathogenic SIV infection

Abstract: Established infections with the human and simian immunodeficiency viruses (HIV, SIV) are thought to be permanent with even the most effective immune responses and anti-retroviral therapies (ART) only able to control, but not clear, these infections1–4. Whether the residual virus that maintains these infections is vulnerable to clearance is a question of central importance to the future management of millions of HIV-infected individuals. We recently reported that ~50% of rhesus macaques (RM) vaccinated with SIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
598
7
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 567 publications
(621 citation statements)
references
References 27 publications
13
598
7
3
Order By: Relevance
“…However, many persistent viral infections such as CMV and EBV in humans lead to CD8 T-cell responses reaching a higher magnitude than most acute infections. Hansen et al (42,43) have recently reported that rhesus macaques vaccinated with persistent rhesus CMV expression vectors containing simian immunodeficiency virus (SIV) proteins elicit durable viral control after challenge with SIV. The studies suggested that the SIV control was linked to a large magnitude of CD8 T cells generated and maintained by the persistent vector at sites of viral entry (mucosa) and at other sites of potential viral dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…However, many persistent viral infections such as CMV and EBV in humans lead to CD8 T-cell responses reaching a higher magnitude than most acute infections. Hansen et al (42,43) have recently reported that rhesus macaques vaccinated with persistent rhesus CMV expression vectors containing simian immunodeficiency virus (SIV) proteins elicit durable viral control after challenge with SIV. The studies suggested that the SIV control was linked to a large magnitude of CD8 T cells generated and maintained by the persistent vector at sites of viral entry (mucosa) and at other sites of potential viral dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Along with the evidence that HIV infections impair the thymic output, this furthermore reveals the retention of T-cells in established chronic infections that can expand substantially 30,31 . The demonstration that virus titers strongly rise following depletion of CD8 + T-cells in SIV infected macaques [32][33][34] and that protective immune responses can be elicited upon vaccinating SIV infected Rhesus macaques 35 further underscore the strong effector capacity of CD8 + T-cells in established chronic infections.…”
Section: Evidence That Functional T-cells Are Maintained In Chronic Imentioning
confidence: 93%
“…A beneficial role for CD8 + T cells in blocking acquisition is less apparent, although this possibility cannot be dismissed. Intriguing studies suggest that CD8 + T-cell responses elicited by a replicating viral vector vaccine can clear a nascent simian immunodeficiency virus (SIV) infection in roughly half of vaccinated nonhuman primates (18). These responses alone did not block acquisition but could contribute to such an effect if combined with certain humoral responses.…”
mentioning
confidence: 99%